Therapeutic plasma exchange in the intensive care unit: Rationale, special considerations, and techniques for combined circuits. (5th December 2022) - Sanchez, Amber P.; Ward, David M.; Cunard, Robyn
Abstract: Therapeutic plasma exchange (TPE) is an extracorporeal blood purification technique with proven efficacy in a variety of conditions, including in the intensive care setting. It is not uncommon for a critically ill patient to require more than one extracorporeal procedure in addition to TPE. This review focuses on the combination of TPE with other extracorporeal circuits in a critical care setting via a single vascular access (either in‐series, parallel, or a hybrid mode) which is often referred to as performing procedures "in tandem." Authors performed literature review via pubmed.gov using search terms: plasma exchange, plasmapheresis, apheresis, tandem circuits, combined circuits, critical care, ICU, CRRT, hemodialysis, and ECMO. Thirty‐eight English‐language, peer‐reviewed papers were appraised that satisfied the content of this review on techniques for combining circuits with plasma exchange, as well as describing the advantages of tandem procedures and potential complications that can arise. Performing these procedures simultaneously can be advantageous in reducing total procedure and staffing time, avoiding placement of additional central lines, reducing overall need for anticoagulation, and limiting multiple blood primes in certain populations. However, the described combined circuits are complex, associated with higher complications, and require a skilled team to understand and mitigate the potential complications associated with these combined procedures.